2021
DOI: 10.1021/acs.cgd.1c00209
|View full text |Cite
|
Sign up to set email alerts
|

Elaborate Supramolecular Architectures Formed by Co-Assembly of Metal Species and Peptoid Macrocycles

Abstract: Peptoids are a family of sequence-specific oligomers capable of mimicking the structure and function of polypeptides. The innate folding and self-assembly capabilities of peptoid oligomers can be enhanced by the presence of coordinated metal ions. In this work, we explore the co-assembly of water-soluble hexameric and tetrameric peptoid macrocycles with Na + and K + ions. Solid-state structures were solved for six cyclopeptoid−metal coassemblies by X-ray diffraction using single crystals grown from fully aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 83 publications
2
16
0
Order By: Relevance
“…To develop an understanding of possible transition paths between the conformations identified in this study, we performed simulations of the conversion between two hexamer conformations: those with tttttt and ttcttc amide patterns. These two simulation results correspond to two conformations discovered co-occupying a position within the unit cell of a recently published crystal structure of Ncm6 . The previously published crystal structures were determined at 100 K; to gain more insight into the thermodynamic properties of these unique conformational features and confirm their relevance under ambient conditions, we redetermined the crystal structures of compound Ncm6 at 295 K in this work.…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…To develop an understanding of possible transition paths between the conformations identified in this study, we performed simulations of the conversion between two hexamer conformations: those with tttttt and ttcttc amide patterns. These two simulation results correspond to two conformations discovered co-occupying a position within the unit cell of a recently published crystal structure of Ncm6 . The previously published crystal structures were determined at 100 K; to gain more insight into the thermodynamic properties of these unique conformational features and confirm their relevance under ambient conditions, we redetermined the crystal structures of compound Ncm6 at 295 K in this work.…”
Section: Resultssupporting
confidence: 61%
“…Due to these many subtle stereochemical features, the energy landscape of cyclic peptoid conformations is highly complex. As mentioned, experimental studies of cyclic peptoids have identified a number of distinct conformations in the solid phase, including two novel structures reported after the initiation of this work 23,24 and a third reported here. Voelz et al have previously demonstrated a method using the Generalized Amber Force Field (GAFF) in molecular dynamics (MD) simulations that reproduces experimental structures 26 and successfully predicted the conformation of a novel cyclic peptoid nonamer.…”
Section: ■ Introductionmentioning
confidence: 62%
See 3 more Smart Citations